All Days 1995
DOI: 10.2118/30687-ms
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects Of Discharge And Reinjection Of Produced Water.

Abstract: There has been much focus on possible acute toxicity of produced water and which natural components and chemicals contributes most to the toxicity. This paper describes a method for risk analyses of discharges to sea based on exposure dose instead of the more common method using concentration. Results are presented from such analyses for the produced water from 4 Norwegian oil/gas fields. A comparison of environmental effects of discharge and reinjection of produced water is also presented based on available m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…A 100% gastrointestinal absorption is considered, as the cancer slope factors were estimated based on administered dose of PAHs. The BTEX aromatic compounds are prominent in produced water, but evaporate rapidly as soon as they are discharged close to the sea surface or from the positively buoyant plumes (Furuholt 1996). For these reasons BTEX were excluded from this study.…”
Section: Resultsmentioning
confidence: 99%
“…A 100% gastrointestinal absorption is considered, as the cancer slope factors were estimated based on administered dose of PAHs. The BTEX aromatic compounds are prominent in produced water, but evaporate rapidly as soon as they are discharged close to the sea surface or from the positively buoyant plumes (Furuholt 1996). For these reasons BTEX were excluded from this study.…”
Section: Resultsmentioning
confidence: 99%
“…A modeling study by Somerville et al (1987) found that even at a 10, 000-m 3 /day discharge rate, a 100-fold dilution was estimated at 50 m from the platform, and a 2800-fold dilution was estimated at 1000 m from the platform. Another modeling study at a low discharge rate (2000 m 3 /day), Furuholt (1996) estimated a 1000-fold dilution would be found at 50 m downstream from the discharge point. Our findings measured similar dilution factors as those predicted by the modeling studies, suggesting that using this detection method, we could obtain measurements comparable with the predicted dilution factors for discharge models.…”
Section: Hibernia Seawater Q-pcr Analysismentioning
confidence: 99%